Perfil clínico e epidemiológico dos pacientes portadores de insuficiência cardíaca internados no hospital universitário João de Barros Barreto, Belém-Pa - MORAES, Joel Campos de (2023)
Heart failure (HF) is a chronic disorder characterized by structural and/or functional failure of the heart muscle. It comprises a public health problem, justified by the high number of cases and hospitalization rate. The study aims to describe the clinical and socio-epidemiological profile of patients with heart failure admitted to Hospital Universitário João de Barros Barreto. This is a retrospective cross-sectional analytical study, carried out at the João de Barros Barreto University Hospital, located in the city of Belém-PA, from June 2020 to December 2021, with patients with heart failure who required hospitalization in the hospital being studied. period between January 2014 and December 2018, with a sample size of 182 individuals. The study was carried out by collecting data from the patients' medical records, using a questionnaire containing questions related to sociodemographic and clinical characteristics. The research was approved by the Research Ethics Committee of the HUJBB/UFPA, assent number 3.805.372. Hospitalizations occurred mainly in females (53.8%) and in the age group ≥ 60 years (69.8%), with a mean age of 67.4 ± 16.1 years; most patients were self- reported of mixed race (80.2%), with family income of up to 1 minimum wage and low education. There was a predominance of hypertensive (10%), chagasic (7%), valvular (4%) and ischemic (3%) etiologies, being considered an undefined etiology in 73% of the individuals included in the sample. The hot and humid clinical-hemodynamic profile prevailed (64%), as well as functional class III (35%), comorbidities of systemic arterial hypertension (43%) and diabetes mellitus (23%). The main causes of HF decompensation were infection (n=106, 58.2%) and poor medication adherence (n=22, 12.1%). Urea and creatinine values were above normal, with mean ± standard deviation, respectively, of 58.6 ± 29.6 and 1.6 ± 1.4. The mean left ventricular ejection fraction was 48.3%, with a predominance of grade I diastolic dysfunction (n=91, 50%). As for the outcome of hospitalizations, 124 (68.1%) patients improved and 55 (30.2%) died. The mortality rate was higher in female patients (61.8%), in the 38 individuals who remained hospitalized for more than 30 days (47.3%) and in those with a hot and humid clinical-hemodynamic profile (49.1%). It is concluded that the longer hospital stay was directly related to the number of deaths, hospitalizations occurred mainly in females and in the age group greater than or equal to 60 years. Chagas' heart disease showed significant relevance among the records, since Pará stands out in the epidemiology of Chagas' disease. Most patients had comorbidities, symptoms mainly related to congestion and intermediate or reduced left ventricular ejection fraction. The clinical outcome of hospitalizations was worse for female patients with longer hospital stays, with the finding of low output associated with congestion showing statistical significance in relation to lethality.